Sistem Informasi Perpustakaan Berbasis Website Menggunakan Metode Agile - Mila Nisti Oktarina; Leon Andretti Abdillah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to design and develop a website-based library information system using the Agile method at SMK Azzahro Palembang. The Agile approach was chosen because it allows for an iterative, flexible, and collaborative software development process between the development team and end users. This process prioritizes speed in completing each development stage and allows for continuous improvement based on user feedback. The developed information system includes several key features, such as book data management, library member data, loan and return transactions, and online book catalog searches. Through this system, library management activities become more structured, efficient, and well-documented. In addition, users—both students and teachers—can easily access book availability information without having to come directly to the library, thus improving time efficiency. The trial results show that this system significantly improves the work efficiency of library staff and user convenience in accessing information. This study also notes the important contribution of the Kampus Mengajar program, which supports the transfer of information technology knowledge to schools and encourages increased digital literacy among students and education personnel. With this information system, it is hoped that library management at SMK Azzahro will be more modern, transparent, and support the school's literacy culture in a sustainable manner. In addition to the practical benefits, the development of this library information system will also have a positive impact on improving digital competency for all elements of the school. Teachers and administrative staff who were previously unfamiliar with intensive digital system use will receive training and mentoring throughout the implementation process. This will result in improved information technology skills that can be applied not only to library management.